Pilocarpus microphyllus seedling growth threatened by climate change: an ecophysiological approach - Amaral, Genilda Canuto; Pezzopane, José Eduardo Macedo; de Souza Nóia Júnior, Rogério; Martínez, Manuel Fernández; Fonseca, Mariana Duarte Silva; Gibson, Elbya Leão; Toledo, João Vitor; Pezzopane, José Ricardo Macedo; Klippel, Valéria Hollunder; Xavier, Talita Miranda Teixeira (Theoretical and applied climatology, 2022)
The climate change endangers many species of the Amazon Forest. An example, in the endangered medicinal species Pilocarpus microphyllus (popularly known as jaborandi). The jaborandi is a natural source of alkaloids used for serious diseases, essential for medical use. However, the potential impacts of climate change on this species are still unknown. Thus, the objective was to evaluate the effect of high temperature and high atmospheric concentrations of CO 2 , projected to occur with climate change, combined with water stress, on the ecophysiology of jaborandi seedlings. For this, seedlings were exposed to three different climatic scenarios in a controlled environment, characterized as current Amazon: RCP4.5 (current Amazon average temperature + 2.5 °C and 538 ppm of [CO 2 ]) and RCP 8.5 (+ 4.5 °C and 936 ppm of [CO 2 ]). Within each climatic scenario, two levels of irrigation were applied: 90% (well-watered) and 40% (water-stressed) of the substrate water holding capacity. Growth variables, plant water status, fluorescence parameters, and enzymatic antioxidants activity were evaluated. The results showed that the jaborandi seedlings showed greater total dry mass production when grown in the current Amazon with no water stress. The seedlings’ growth was negatively affected by the scenarios enriched with CO 2 , especially RCP 8.5. Climate change scenarios had the greatest negative impact when the seedlings were subject to water stress. Under these scenarios of climate change and water stress, the seedlings allocated more carbohydrates to the root system. The negative effect of water stress on jaborandi physiology and growth was attenuated by the RCP 8.5 scenario. Our results indicated that the predicted climate changes negatively impact ecophysiology jaborandi, being a threat to the extinction of this species.